Effectiveness of a New Single‐Needle Single‐Pump Dialysis System with Simultaneous Monitoring of Dialysis Dose. Issue 8 (16th April 2018) - Bieser, Wolfgang; Welsch, Markus; Jakob, Marten; Meibaum, Jörn; Rodriguez, David A.; Wolff, Henrik; Marcelli, Daniele; Barth, Claudia
Abstract: To date, single‐needle (SN) hemodialysis (HD) requires a dialysis machine equipped with two blood pumps—one controlling arterial blood flow (Qb) and one controlling venous Qb. B. Braun has developed an innovative single‐pump SN HD system. Therefore, usability is improved by reducing complexity. The aim of this study was to compare dialysis parameters of the new single‐pump SN HD system with a double‐pump SN HD system available on the market (Fresenius Medical Care [FMC] 5008). In this two‐armed crossover study, patients were randomized into two groups (B. Braun ‐ FMC/FMC ‐ B. Braun). Study period was 2 weeks (6 HD sessions) for each SN HD system. Both B. Braun and FMC dialysis machines were operated in the single‐needle auto mode. With the FMC dialysis machines, Qb was optimized manually, whereas for B. Braun machines it was optimized automatically using the auto‐mode functionality. A phase volume of 25 mL, treatment time, needle type and size, and dialyzer type and size were kept constant per patient throughout the study. Due to technical prerequisites in the SN mode, online dialysis adequacy ( Kt / V : K ‐ dialyzer clearance of urea; t ‐ dialysis time; V ‐ volume of distribution of urea) monitoring could only be performed in the B. Braun group. Twelve HD patients (5 male/7 female, mean age 75.5 ± 8.8 years, mean time on dialysis 4.97 ± 3.86 years, 3× weekly HD) were enrolled. Total number of treatments performed: n  = 132 (65 B. Braun, 67 FMC) and the mean online Kt / V value in the B. Braun group was 1.26 ± 0.29 ( n  = 63). Mean dialysis time per session: B. Braun 253.4 ± 19.9 min, FMC 251.6 ± 18.8 min. Mean phase volume: B. Braun 25.1 ± 0.2 mL, FMC 25.4 ± 3.1 mL. Mean cumulated blood volume (CBV): B. Braun 55.0 ± 5.5 L, FMC 40.5 ± 5.9 L ( P  < 0.0001). Mean Qb: B. Braun 217.8 ± 12.9 mL/min, FMC 178.6 ± 14.9 mL/min (effective Qb) ( P  < 0.0001), which corresponds to a difference of 39.3 mL/min (22.0%). Higher Qb has an influence on the CBV. To evaluate this effect, CBV was corrected for the difference in Qb by calculating the CBV/Qb rate. The mean CBV/Qb rate was 252.2 ± 19.4 min (B. Braun) and 226.8 ± 27.6 min (FMC) ( P  < 0.0001) per session. This represents a highly significant difference of 11.4%. To support the in vivo data the dead time for opening/closure of the clamps of the FMC 5008 was measured, resulting in 364 milliseconds. Over a 240 min dialysis session, with a blood flow rate of 250 mL/min and a phase volume of 25 mL, it was estimated at about 14.56 min (6.1% of the session). Similarly, it was estimated that the dead time of the pumps of the FMC 5008 during 240 min dialysis session was 4.7 min (1.9% of the session). In case single needle therapy is the only practical option for a patient, the advantages of the new single‐pump single needle system—namely the proven higher cumulative blood volume, the alarm‐free auto‐regulation of the blood flow and the easier handling for the nursing staff—ensure higher treatment efficiency than conventional double‐pump single needle systems.